Improving Students’ Literacy: Successful Efforts of the School Literacy Movement (SLM) In Muhammadiyah Kisaran of Elmentary School - Permata Sari, Putri Lidiana; Supiatman, Lis; Aryni, Yen (Universitas Pahlawan Tuanku Tambusai, 2023)
Literacy includes the ability to listen, speak, read, and write in a way that allows a person to communicate effectively. In addition, literacy also includes matters relating to vocabulary, spelling, understanding, language sounds, to the relationship between letters and sounds.In AKM, literacy focuses on reading ability which can be defined as an ability to understand, use, evaluate, and reflect on various types of written texts. This ability is developed so that students can deepen lessons or other knowledge more quickly and can apply the understanding gained more broadly in everyday life.Competencies assessed in reading literacy skills include logical and systematic thinking skills, reasoning with concepts and knowledge, as well as the ability to process the information obtained.Content in reading literacy includes informational texts and fictional texts. At the cognitive level, literacy skills are assessed from components including finding information, interpretation and integration, as well as evaluation and reflection. While in context, the components of reading literacy include personal, socio-cultural, and scientific.